Cardiovascular Imaging-Derived Skeletal Muscle Mass Correlates With Fitness and Survival in Patients With Univentricular Circulation - Illinger, Vojtěch; Slabý, Kryštof; Suchánek, Vojtěch; Radvanský, Jiří (Curēus, 2024)
Aims This study aims to retrospectively quantify skeletal muscle mass from cardiovascular imaging studies in total cavopulmonary connection (TCPC) patients and to correlate calculated muscle mass with clinical outcomes. Materials and methods Ninety-one TCPC patients at a mean age of 24.0 ±5.5 years (37 women; 40.7%) who underwent chest computed tomography (CT) or cardiac magnetic resonance imaging (MRI) as part of their follow-up were identified in a single-center database. The cross-sectional skeletal muscle index (SMI) at the Th4 and Th12 levels was calculated from CT images, and the dorsal skeletal muscle area (SMA) at the Th12 level was measured from an MRI. Results Calculated SMI at Th12 level was 38.0 (34.5; 42.0) cm2.m-2 or 89.6 (81.9; 101.6) % of predicted values. The median follow-up from CT was 5.9 (3.1; 8.5) years, and the composite endpoint (death N=5, heart transplant N=6) was reached in a total of 11 (26.8%) patients. Patients with SMI (Th12) less than 90% of predicted values had a hazard ratio of 5.8 (95% CI: 1.2; 28.3) (p=0.03) for endpoint achievement. In the MRI group, dorsal SMA at the Th12 level was 27.6 ±5.1 cm2 in men and 20.0 ±5.8 cm2 in women. Correlations were found between SMA/kg and peak oxygen uptake (VO2 peak) (r=0.48, p=0.0005) and fat-free mass (r=0.63, p<0.0001), respectively. Conclusions A low SMI at the Th12 level was associated with a higher risk of death or cardiac transplantation. Evaluation of skeletal muscle mass using cardiovascular imaging methods allows rapid identification of individuals at risk of sarcopenia.